Zaleya decandra exerts anti-cancer activity in HCT-116 cancer cells by impairing mitochondrial activity (Bangladesh Journal of Pharmacology, 2019)
An attempt has been made to investigate the role of Zaleya decandra on the survival of HCT colon cancer cells in vitro. The cell viability and apoptosis were assessed using MTT assay and acridine orange/ethidium bromide staining, respectively. Mitrochondrial membrane permeability was assessed using rhodamine-123 staining. The activities of caspases were evaluated using ELISA kits. Treatment with Z. decandra extract increased the production of ROS in HCT cells and impaired the mitochondrial activity as evidenced by decreased reduction of tetrazolium salt and enhanced mitochondrial membrane permeability. The onset of apoptosis was evident in cells treated with the extact in acridine orange/ethidium bromide staining and was associated with elevated levels of initiator and effector caspases in the conditioned medium. In conclusion, Z. decandra treatment promoted the apoptosis of HCT colon cancer cells.Video Clip of Methodology:6 min 53 sec:  Click to watch